Adequate exposure to tacrolimus with sublingual administration in pediatric liver transplant patients - Riva, Natalia (2017)
Fil: Riva, Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Gobierno de la Ciudad de Buenos Aires. Hospital de Pediatría "Juan P. Garrahan"; Argentina